Some key moments in developing technical playing skills - Gricius, A. (Psichologija, 1964)
The prevailing attitude in music pedagogy, that a singer-instrumentalist can be prepared in two stages, one technical and another artistic, separately, is false. Regardless of the type of technical skill developed at a given moment, it cannot be abstracted from how it sounds, from the quality of it. The student/performer absolutely must be tough holistically in order to achieve harmony between technical and musical ability. Before beginning any type of technical work, and clear and powerful sound design must already exist in your mind. In most cases the inner ear, or what you’re hearing in your head, lacks two very important components for the performer/instrumentalist, i.e. timbre and rhythm. There have also been a number of cases when vocal motility (soundless throat, tongue, and lip movement) is used to cause a sound image. In this case the sound image typically has a range of personal voice qualities that is limited by the performer’s imagination. Although the method may be appropriate in the first stage of learning when the musician/performer must first and foremost learn accurate intonation, later it is not: next, and play what you’re hearing in your head mode commences, including agility, specific timbre of a given instrument, inner hearing, and vocal-based motility. Images are closely related to actual impressions. Therefore, to develop the inner ear, you have to listen to as much audio as possible, both live and recorded—practice listening to the sound impressions. In addition, there are ways to develop the right internal auditory characteristics based on primary visual memory and the so-called "mixed inner ear" (the ability to continue a tune hearing only the start). If at first, while training a technical skill, you can focus on one or another detail of movement of movement analysis (remembering always the musical task), later any attention diverted to these will cut short the automation and synthesis of skills. The teacher’s task is to direct the student’s attention in a specific way at the correct moment.